Pengaruh Visual Merchandising, Promosi Penjualan, dan Kualitas Produk Terhadap Keputusan Pembelian di KKV DP Mall Semarang - Istiyanti, Mutiara; Herlinudinkhaji, Didin; Ramadhani, Lingga Kurnia (JULIUS (Journal of Digital Business); Vol 2 No 1 (2024): JULIUS, 2024)
The rapid development of times and business has led to many retail companies competing to try to meet economic needs. Strategic competition between retail companies is getting tighter in attracting consumers because of the various choices of retail stores. This study aimed to determine the level of influence of visual merchandising, sales promotion, and product quality on purchasing decision at KKV DP Mall Semarang. In this study, a quantitative method was used with a purposive sampling technique using a questionnaire. The number of samples in this study was 120 respondents. The data was processed using the SEM–PLS technique. The evaluation results show that visual merchandising and sales promotion have no influence on purchasing decisions and product quality has a significant positive influence on purchasing decision.